Virtual reality and augmented reality applications and simulation in vascular access management with three-dimensional visualization. Issue 1 (May 2019) - Yokoyama, Itsuo; Sarai, Tsuyosi; Asai, Toshinori; Kitou, Nobuyuki; Nozaki, Hirotaka; Kondo, Yuki; Nomura, Yusaku; Morizane, Atsushi; Sekikawa, Michi; Liu, Dage
Obtaining adequate and precise anatomical information is mandatory to prevent vascular access–related complications in dialysis patients. For this purpose, we underwent Doppler ultrasound, vascular access angiogram, and plain computer-assisted tomography scan of the arm with vascular access. With the use of computer graphics software, the anatomical structure of the vascular access can be visualized three dimensionally which is shared among the staffs for precise and better recognition. Furthermore, created object is applicable for virtual reality and/or augmented reality presentation that provides useful means for education and practical procedures in the management of vascular access.